Kode Etik Guru Pendidikan Agama Kristen dalam Kebebasan Media Sosial - Napa, Misrini; Triposa, Reni (Sekolah Tinggi Agama Kristen Diaspora, 2023)
The code of conduct of teachers of Christian religious education in the freedom of social media. The code of ethics has a role and becomes very important for education. Because the code of ethics is an ethic that must be possessed by all teachers, especially for Christian religious education teachers. This code of ethics has the ability to guide teachers and can understand learners well. Christian religious education teachers, which currently still lack the application of Christian religious education, are a challenge for education in the digital era. With this research, it has the aim of providing understanding for every educator, especially Christian religious education teachers, so that they can be an example and example for their students in the process of teaching and learning. Christian religious education teachers are teachers who are role models and are able to bring every student in this digital era, where every student knows and uses social media. This research uses a qualitative method, namely by studying literature to collect various sources of scientific data, both articles, journals and books. The sources of data collected are appropriate and related to observations, namely the facts that occur in the field. The result of this research is that Christian religious education teachers must be able to be role models and live Christian values and make the Lord Jesus an example, before sharing or being an example for their students. Because Christian religious education teachers already have a good and correct code of ethics, it will be reflected and can produce students with the character of Christ.AbstrakKode etik guru pendidikan agama Kristen dalam kebebasan media sosial. Kode etik mempunyai peran dan menjadi sangat penting bagi pendidikan. Karena kode etik merupakan suatu etika yang harus dimiliki oleh semua guru, terutama bagi guru pendidikan agama Kristen. Kode etik ini memiliki kemampuan untuk membimbing guru dan dapat memahami peserta didik dengan baik. Guru pendidikan agama Kristen yang saat ini masih adanya kurang penerapan pendidikan agama Kristen merupakan tantangan tersendiri bagi pendidikan di era digital. Dengan adanya penilitian ini memiliki tujuan dimana memberikan pemahaman bagi setiap pendidik terutama guru pendidikan agama Kristen agar bisa menjadi contoh dan teladan bagi peserta didiknya dalam berlangsungnya proses belajar mengajar. Guru pendidikan agama Kristen merupakan guru yang menjadi teladan dan mampu membawah setiap peserta didiknya di era digital ini, dimana setiap para peserta didik mengenal dan memnggunakan media sosial. Penelitian ini menggunakan metode kualitatif yaitu dengan studi Pustaka mengumpulkan berbagai sumber data ilmiah baik artikel, jurnal dan buku. Sumber-sumber data yang dikumpulkan sesuai dan berkaitan dengan dari pengamatan yaitu fakta-fakta yang terjadi di lapangan. Hasil dari penelitian ini adalah guru pendidikan agama Kristen harus mampu menjadi teladan dan menghidupi nilai-nilai Kristen dan menjadikan Tuhan Yesus sebagai teladan, sebelum membagikan atau menjadi teladan bagi para peserta didiknya. Karena guru pendidikan agama kristena sudah mempunyai kode etik yang baik dan benar maka itu akan tercermin dan dapat menghasilkan peserta didik yang berkarakter Kristus.